Transcriptome profiling of Cucumis metuliferus infected by Meloidogyne incognita provides new insights into putative defense regulatory network in Cucurbitaceae - Jian Ling (Nature Portfolio, 2017)
Abstract Root-knot nematodes (RKN) represent extensive challenges to Cucurbitaceae crops. However, Cucumis metuliferus (Cm) is known to be resistant to Meloidogyne incognita (Mi) infections. Thus, analysis of differentially expressed genes may lead to a comprehensive gene expression profiling of the incompatible Cm-Mi interaction. In this study, the time-course transcriptome of Cm against Mi infection was monitored using RNA-Seq. More than 170000 transcripts were examined in Cm roots, and 2430 genes were subsequently identified as differentially expressed in response to Mi infection. Based on function annotation and orthologs finding, the potential mechanism of transcriptional factor, cytoskeleton, pathogen-related genes and plant hormone were assessed at the transcription level. A comparison of gene expression levels between Mi-infected Cm and cucumber plants revealed that cytoskeleton-related genes are key regulators of Cm resistance to Mi. We herein discuss the dual nature of cytoskeleton-related genes in the susceptibility and resistance of plant hosts to Mi. Our observations provide novel insights into the responses of Cm to Mi at the transcriptome level. The data generated in this study may be useful for elucidating the mechanism underlying resistance to RKNs in cucurbitaceous crops.